2023
DOI: 10.3389/fgene.2023.1125097
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of meiotic genes in male vs. female gonads and gametes: Insights into fertility issues

Abstract: Gametes are specialized cells that, at fertilization, give rise to a totipotent zygote capable of generating an entire organism. Female and male germ cells undergo meiosis to produce mature gametes; however, sex-specific events of oogenesis and spermatogenesis contribute to specific roles of gametes in reproductive issues. We investigate the differential gene expression (DGE) of meiosis-related genes in human female and male gonads and gametes in normal and pathological conditions. The transcriptome data for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Interestingly, the co-expression network demonstrated that the four validated SCMC genes are co-expressed with genes related to male reproduction. Interestingly, a previous work of our group evidenced OOEP downregulation in patients with teratozoospermia or non-obstructive azoospermia ( Rockenbach et al, 2023 ), evidencing possible new roles for the SCMC genes in both embryonic development and in female and male reproduction. Moreover, the results presented here shed light on a possible role of SCMC gene expression profile in later reproductive conditions, such as in post-implantation gestational events.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, the co-expression network demonstrated that the four validated SCMC genes are co-expressed with genes related to male reproduction. Interestingly, a previous work of our group evidenced OOEP downregulation in patients with teratozoospermia or non-obstructive azoospermia ( Rockenbach et al, 2023 ), evidencing possible new roles for the SCMC genes in both embryonic development and in female and male reproduction. Moreover, the results presented here shed light on a possible role of SCMC gene expression profile in later reproductive conditions, such as in post-implantation gestational events.…”
Section: Discussionmentioning
confidence: 62%
“…Although the SCMC is confirmedly present only in oocytes and early embryos ( Li et al., 2008b ; Zhu et al, 2014 ), it is not settled whether the proteins of the SCMC could act as single molecules in other tissues, not being aggregated to form the multi-protein complex. Literature reports based on the evaluation of conditions such as male fertility ( Rockenbach et al, 2023 ), and imprinting disorders ( Eggermann et al, 2021 ), have helped to instigate this hypothesis. However, not limited to tissue variability, we speculate whether the individual members of the SCMC could have roles in processes such as embryonic implantation and even in later steps, such as the maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 99%